2016
DOI: 10.1002/ccd.26430
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical follow‐up of patients undergoing percutaneous alcohol septal reduction for symptomatic obstructive hypertrophic cardiomyopathy

Abstract: In this long-term clinical follow-up without losses, ASA was effective in improving quality of life and NYHA functional class, with relatively low mortality and very low need for immediate permanent pacemaker implantation. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The articles describing the experiences of patients with HCM identified in the literature review revealed shortness of breath or dyspnea, chest pain (angina) [31,32], and fainting (syncope) [31][32][33] to be the primary complaints/symptoms of patients with HCM.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The articles describing the experiences of patients with HCM identified in the literature review revealed shortness of breath or dyspnea, chest pain (angina) [31,32], and fainting (syncope) [31][32][33] to be the primary complaints/symptoms of patients with HCM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, all three HCM professional guideline documents describe patients with HCM as having common symptoms of dyspnea, palpitations, chest pain (angina), and fainting (syncope) [1,3,4]. Furthermore, the literature review identified fatigue [4], tachyarrhythmia [32,33], orthopnea [9], pulmonary congestion [1], excessive sweating [4], and heart failure [4,33] as additional symptoms experienced by some patients with HCM.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles describing the experiences of patients with HCM identi ed in the literature review revealed shortness of breath or dyspnea, chest pain (angina) (30,31), and syncope (30)(31)(32) to be the primary complaints/symptoms of patients with HCM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, all three HCM professional guideline documents describe patients with HCM as having common symptoms of dyspnea, palpitations, chest pain (angina), and syncope (1, 3, 4). Furthermore, the literature review identi ed fatigue (4), tachyarrhythmia (31,32), orthopnea (9), pulmonary congestion (1), excessive sweating (4), and heart failure (4, 32) as additional symptoms experienced by some patients with HCM.…”
Section: Literature Reviewmentioning
confidence: 99%